Comprehensive evaluation of the water-fertilizer coupling effects on pumpkin under different irrigation volumes - Zhong, Tao; Zhang, Jinxia; Du, Liangliang; Ding, Lin; Zhang, Rui; Liu, Xingrong; Ren, Fangfang; Yin, Meng; Yang, Runheng; Tian, Pengliang; Gan, Kaiyuan; Yong, Tian; et al. (Frontiers in Plant Science, 2024)
Abstract: The northwest arid region of China have long suffered from the issues of poor crop growth, low yields, and inefficient use of water and fertilizer under traditional irrigation and fertilization. Water-fertilizer coupling can improve crop growth and enhance yields by increasing water and fertilizer use efficiency. Therefore, a two-year on-farm experiment in 2022 and 2023 was conducted to study the effects of water-fertilizer coupling regulation on pumpkin growth, yield, water consumption (ET), and water and fertilizer use efficiency. Simultaneously the comprehensive evaluation of multiple objectives was carried out using principal component analysis (PCA) methods, so as to propose an suitable water-fertilizer coupling regulation scheme for the region. The experiment was set up as a two-factor trial using water-fertilizer integration technology under three irrigation volume (W1=37.5 mm, W2=45.5 mm, W3=52.5mm) and three organic fertilizer application amounts (F1=3900-300 kg ha-1, F2=4800-450 kg·ha-1, F3=5700-600 kg·ha-1), with the traditional irrigation and fertilization scheme from local farmers as control treatments (CK). The results indicated that irrigation volume and organic fertilizer application significantly affected pumpkin growth, yield, and water and fertilizer use efficiency (P<0.05). Pumpkin yield increased with increasing irrigation volume.Increasing organic fertilizer levels within a certain range benefited pumpkin plant growth, dry matter accumulation, and yield, however, excessive application beyond a certain level had inhibited effects on those. The increased fertilizer application under the same irrigation volume enhanced the efficiency of water and fertilizer utilization. However, excessive irrigation only leads to ineffective water consumption, reducing the efficiency of water and fertilizer utilization. However excessive irrigation only resulted in inefficient water consumption, reducing the water and fertilizer use efficiency. The Comprehensive evaluation by PCA revealed that the F2W3 treatment outperformed all the others, effectively addressing the triple objectives of increasing production, improving efficiency, and promoting green production. Therefore, F2W3 (Irrigation volume: 52.5 mm; Fertilizer application amounts: 4800-450 kg/ha-1) as a water and fertilizer management scheme for efficient pumpkin production in the arid region of northwest China.